Analýza trhu bytových jednotek - Vysočina - Hejdová, Michaela; Hejdová Michaela (České vysoké učení technické v Praze, 2018)
Tématem diplomové práce je Analýza trhu bytových jednotek - Vysočina. V teoretické části jsou vysvětleny pojmy, které slouží jako podklad pro praktickou část. Dále jsou analyzovány faktory, které ovlivňují cenu nemovité věci. V praktické části je provedena podrobná analýza trhu bytových jednotek pro kraj Vysočina. Jsou zde porovnávány hodnoty nájmů bytů nabízených na trhu a bytů, které vlastní město. Dále je spočítána návratnost investice do bytů. Výsledným cílem diplomové práce je analyzování trhu s byty v kraji Vysočina.

The theme of this thesis is Analysis of the apartment market - Vysočina. The theoretical part deals with the terms that are used as a basis for the practical part. Various factors that influence the price of a real estate are analysed there too. The practical part contains a detailed analysis of the housing units market related to the Vysočina Region. Rental values of the apartments that are offered on the market and the apartments owned by the city are also compared in this part. Furthermore, the return on investment on apartments is calculated. The final aim of the thesis is to thoroughly analyse the housing units market in the Vysočina Region.
Analysis of the apartment market - Vysočina
Keywords: analýza trhu,nemovitá věc,bytová jednotka,koupě,pronájem,návratnost investice; market analysis,real estate,housing unit,purchase,rental,return on investment